The Integration of Quantum Physics in the Transformation of Consciousness in Individuals, Couples and Organizations - Gregory, Bruce; Gregory, Birgitta (Journal of Psychology and Psychotherapy Research, 2014)
This paper explores the role of the dynamics and principles of quantum physics in the transformation of consciousness. Quantum entanglement, momentum, the uncertainty principle, Dirac’s creation and destruction operators, and the role of opposites are discussed in the contexts of the implied directive, group theory, and the transformation of resistance with individuals, couples, and organizations. The appreciation of novelty, the role of focusing attention, and the needs for depth and containment are explored in the context of recent developments of neuroscience. These developments are explored in the context of applications from set and group theory. Erickson’s resistance protocol is utilized as both a template and metaphor for the role of the consciousness of the professional and the integration of quantum principles and dynamics in the transformation of consciousness.